UKRAINIAN PATRIOTISM OF JULIUSZ SŁOWACKI - Павличко, Д. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
For the first time into the Ukrainian language, this study reveals the Ukrainian identity of the outstanding Polish romantic poet.